PERSEPSI KESANTUNAN DIREKTIF BAHASA INDONESIA MAHASISWA PRODI PENDIDIKAN BAHASA DAN SASTRA INDONESIA FKIP UNIVERSITAS MUHAMMADIYAH KOTABUMI - Masitoh Masitoh (Universitas Muhammadiyah Kotabumi, 2021)
One of the function of language is a communication tool. The form of the respect and appreciation of the person to others when communicating is to use polite and courteous language. Therefore, in this research article, the problem that would be discussed was “The Perceptions of Directive Politeness in Indonesian language for the students of Indonesian Language and Literature Education Study Program”. The purpose of this research was to describe the directive politeness in Indonesian language for the students of Indonesian Language and Literature Education Study Program. The quantitative descriptive method was applied in this research by describing the frequency of the politenes in Indonesian language for the students of Indonesian language and literature education study program. Furthermore, it was describe the differences perception of the politeness for the students of Indonesian language and literature of education who in Lampung ethnic and Javanese ethnic: between male students of Lampung and Javanese ethnicity, between female students of Lampung and Javanese ethnicity as it is. The questionnaire was applied in this research to get the data on the directives politeness in Indonesian language.The questionnaire contains a context that consisting of 20 questions followed by nine multiple choices of directive speech act from impolite, less polite to polite. The nine sequences of directive speech acts are: A. Imperative sentence/Kalimat Imperatif (KI), B. Explicit Performative Sentence/Kalimat Performative Eksplisit (KPE), C. Gated Performative Sentence/Kalimat Performative Berpagar (KPB), D.Statement of Desire/Pernyataan Keinginan (PI), F. Formulation of Suggestions/Rumusan Saran (RS), G. Preparation of Questions/Persiapan Pertanyaan (PP), H. Strong Signals/Isyarat Kuat (IK), and I. Soft Signs/ Isyarat Halus (IH). The result of the research was there were significant differences and similarities in the perception of the Indonesian Language in directive politeness of Lampung and Javanese ethnic students. The differences perception of directive politeness in Indonesian language of Lampung and Javanese ethnic students were in the statement A, B, D, F, G, H, and I; the similarity perception of directive politeness in Indonesian language of Lampung and Javanese etchnic students were in statements C and E. This differences could occur because of the cultural differences. There was a similarity in the preception of directive politeness in Indonesian language of Lampung and Javanese ethnic students because the two languages have the same level in language.